Effects of different limit strength on plastic strains of thick walled pressure vessels - Guven, Ugur (ELSEVIER SCI LTD, 2013)
In this work, the effects of intermediate principal stress and different limit strength on the maximum plastic strain distributions for the cylindrical and spherical pressure vessels are investigated. The present analytical solution is based on unified strength criterion. The aim of this work is to give a reliable theoretical tool for the predictions of plastic strain distributions of the cylindrical and spherical pressure vessels. The numerical results including Poisson's ratio effect are presented graphically and discussed. Consequently, it can be observed that to be the significant differences between the present and previous solutions. In particular, it can be seen that these differences are more significant, for many materials having the same limit strength used frequently in the practical applications. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thick walled vessels; Internal pressure; Strength different; Unified strength criterion; Plastic strains; STEELS; Engineering